Proposing a quick assessment tool for heavy vehicle commercial drivers’ fatigue in oil and gas industry of Malaysia - Isha, A.S.N.B. (American Scientific Publishers, 2017)
Heavy vehicle commercial drivers possess a vibrant role in the transportation industry. Driver’s fatigue is one of the most important concerns for the transportation business. The extant literature review indicated that many factors are contributing to driver’s fatigue but still, there is a dire need to explore other factors that can influence heavy vehicle driver’s fatigue in the case of Malaysian Oil and Gas Industry. Hence, the study aims to identify the factors contributing to the heavy vehicle driver’s fatigue and develop a quick assessment tool for this Industry. A mix method approach will be used for data collection. We aim to select heavy vehicle drivers as unit of analysis. The findings of the study will contribute to heavy vehicle driver’s fatigue and further enhance the fatigue literature. Identified indicators will be further used to develop a quick assessment tool for the heavy vehicle commercial driver’s fatigue. © 2017 American Scientific Publishers. All rights reserved.